2020
DOI: 10.1186/s13089-020-00181-8
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of postural lung recruitment maneuver in children: a randomized, controlled study

Abstract: Background: Pulmonary atelectasis in anesthetized children is easily reverted by lung recruitment maneuvers. However, the high airways pressure reached during the maneuver could negatively affect hemodynamics. The aim of this study is to assess the effect and feasibility of a postural lung recruitment maneuver (P-RM); i.e., a new maneuver that opens up the atelectatic lung areas based on changing the child's body position under constant ventilation with moderated driving pressure (12 cmH 2 O) and of positive e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(50 citation statements)
references
References 32 publications
1
48
0
1
Order By: Relevance
“…We are not aware of any study that has compared pre-mortem with post-mortem LUS findings, and pre-mortem LUS was not performed on our patients. Therefore, for the post-mortem analysis, we used LUS parameters previously established in vivo [ 2 , 3 , 5 , 7 , 26 ]. To our knowledge, this is the first study to correlate ultrasound imaging with histological injury in COVID-19 patients; our results provide additional information to the previous in vivo imaging studies and reinforce the concept that LUS is accurate enough to track the extent of fibroproliferative alveolar damage in severe COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We are not aware of any study that has compared pre-mortem with post-mortem LUS findings, and pre-mortem LUS was not performed on our patients. Therefore, for the post-mortem analysis, we used LUS parameters previously established in vivo [ 2 , 3 , 5 , 7 , 26 ]. To our knowledge, this is the first study to correlate ultrasound imaging with histological injury in COVID-19 patients; our results provide additional information to the previous in vivo imaging studies and reinforce the concept that LUS is accurate enough to track the extent of fibroproliferative alveolar damage in severe COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…We defined for each of the eight sites of study a binary indicator (0 = absence; 1 = presence) of LUS parameters previously described in several studies dedicated to assess the severity of pulmonary COVID-19 [ 2 , 5 , 26 ], as follows: normal pleural line, irregular pleural line, fragmented pleural line, A lines, spaced B lines, confluent B lines (sometimes giving the appearance of a white lung), peripheral consolidation, and pulmonary consolidation. For each patient, values of LUS parameters were calculated as the sum of the scores obtained at the eight examined sites (therefore, the value of each LUS parameter varied from 0 to 8 for each patient).…”
Section: Methodsmentioning
confidence: 99%
“…This is the rst description of using EIT with targeted lateral positioning to personalize PEEP in adult patients with COVID-19-associated ARDS. A randomized and controlled trial demonstrated the feasibility and e cacy of a postural recruitment maneuver in children with anesthesia-induced atelectasis [7]. Besides being applied in children with healthy lungs, another difference between the Acosta et al and our study is the lack of PEEP titrations.…”
Section: Discussionmentioning
confidence: 72%
“…Very recently, Zhao et al reported the use of EIT for individualized ventilation strategy in one patient with COVID-19 [8]. Similarly to the study in children with anesthesia-induced atelectasis [7], a key difference between the Zhao et al case report and our case series is the lack of a strategy to personalize PEEP during the lateral positioning.…”
Section: Discussionmentioning
confidence: 81%
“…This is the first description of using EIT with targeted lateral positioning to personalize PEEP in adult patients with COVID-19-associated ARDS. A randomized and controlled trial demonstrated the feasibility and efficacy of a postural recruitment maneuver in children with anesthesia-induced atelectasis [ 10 ]. Besides being applied in children with healthy lungs, another difference between the Acosta et al and our study is the lack of PEEP titrations.…”
Section: Discussionmentioning
confidence: 99%